The use of a new oral antiviral drug molnupiravir in the treatment of COVID-19 from a safety perspective - A. L. Khokhlov; J. V. Rybachkova (Izdatelstvo OKI, 2022)
Molnupiravir is an antiviral drug with a broad spectrum of activity against RNA viruses. The safety of molnupiravir in clinical trials with COVID-19 was analyzed. In a Phase I study (NCT04392219), molnupiravir was well tolerated at doses of 50 to 800 mg twice daily for 5.5 days and at single doses up to 1600 mg. Common adverse events were headache (18.8 % placebo versus 12.5 % molnupiravir) with a single dose and diarrhea (7.1 % in both groups) with multiple doses. In a phase II study in the molnupiravir 800 mg group, adverse events were noted in the form of headache, insomnia, and an increase in the level of alanine aminotransferase. Serious adverse events leading to hospitalization occurred in the placebo group (1.6 %) due to hypoxia, in the molnupiravir 400 mg group in two (3.2 %) participants due to cerebrovascular accident and in one (1.8 %) of a participant at a dose of 800 mg due to acute respiratory failure. In the phase III MOVe-OUT study (NCT04575597), adverse events were reported in 30.4 % in the molnupiravir group and 33.0 % in the placebo group. In the phase III study CTRI/2021/06/033992, adverse events occurred in 6.5 % in the molnupiravir group versus 8.9 % in the placebo group. The results of the conducted studies demonstrate the safety, tolerability of molnupiravir in phase I, II and III clinical trials and the antiviral efficacy of the drug against COVID-19. Use of molnupiravir for mild to moderate (SpO2 > 93 %) COVID-19 within 5 days of symptom onset significantly reduces disease progression by reducing hospitalizations and/or deaths.